Influence of transition metal ion (mn4+) on mullite formation in a mixture of 50:50 Nigerian kaolin and calcined alumina. Issue 1 (1st January 2017) - Aladesuyi, Olanrewaju; Pal, Mousumi; Emetere, Eterigho Moses; Das, Swapan Kumar; Ajanaku, Kolawole Oluseyi
Abstract: In the present investigation, 5 wt% chemical grade MnO2 was added in a mixture of 50:50 Nigerian sources of kaolin and superfine calcined alumina powder and effect of this transition metal ion on their physico-mechanical properties, phase and microstructural evolution were studied during heating in the temperature range of 1, 400–1, 650°C. The heated samples were found to be highly porous (>30%) in this entire temperature range. The doping of 5 wt% MnO2 in this mixture did not improved the densification, but resulted into higher flexural strength (26 MPa) at 1, 400°C compared to 7 MPa in the undoped sample. At 1, 650°C, the reverse trend was observed, the flexural strength of undoped sample was found to be higher (38 MPa) than doped sample (27 MPa). The XRD study revealed the formation of mullite as major and corundum as minor phases in both the samples. The microstructural study shown the presence of needle shaped mullite crystals and corundum grains. The presence of inter-granular and intra-granular pores in MnO2 doped samples might have reduced the strength at 1, 650°C. The aspect ratio of mullite needle at 1, 650°C was found to be higher in doped sample. The theoretical and experimental value of >4 for MnO2 ion has been validated.